2005
DOI: 10.2320/matertrans.46.1775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment on Microstructures and Physical Properties of Segmented Thermal Barrier Coatings

Abstract: Highly segmented thermal barrier coatings (TBCs) were produced by ''hot'' plasma spraying. The effects of heat treatment on the microstructures, mechanical and thermophysical properties were studied. The segmented coatings are denser than traditionally plasma-sprayed TBCs due to its good insplat bonding at high substrate temperature. The segmentation cracks and associating branching cracks hardly propagated or closed during sintering process, indicative of a good stability of crack network. Due to its low poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…The small pore sizes are mainly attributed to microcracks and intersplat gaps within the coating. [26][27][28][29] When the YSZ coating was held at 1250 • C, the glassy CMAS penetrated into the coating quickly and filled most of the open porosities which led to the significant reduction in porosity.…”
Section: Effect Of Cmas Deposits On Ysz Coating Microstructurementioning
confidence: 99%
“…The small pore sizes are mainly attributed to microcracks and intersplat gaps within the coating. [26][27][28][29] When the YSZ coating was held at 1250 • C, the glassy CMAS penetrated into the coating quickly and filled most of the open porosities which led to the significant reduction in porosity.…”
Section: Effect Of Cmas Deposits On Ysz Coating Microstructurementioning
confidence: 99%
“…As a multilayer system with BC, TGO, and top coat stacking sequentially on substrate, the delamination‐resistance of TBCs is highly relevant to the performance of all constituent parts. It is believed that the inducements of TBC failure are as follows: (1) the thickening of TGO; (2) the phase transformation induced volume expansion of top coat; (3) the sintering of top coat . All these three types of failure mechanisms can be attributed to the large strain and stress resulting from the meta‐stable phases and microstructures mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…This has a detrimental effect on the strain tolerance of top coat . In addition, the sintering of top coat also leads to an increase in thermal conductivity, resulting in distinct degradation on the thermal barrier performance …”
Section: Introductionmentioning
confidence: 99%
“…It has thus been of interest to examine the change in microstructure, stiffness, and thermal properties of the APS YSZ system subjected to continuous and cyclic thermal exposures. A large portfolio of scientific literature exists for both such attributes with exposure of free‐standing sprayed bodies to various temperatures and times . Specifically, a number of studies have reported the variation in the elastic modulus with sintering and attempted correlation with the variation in elastic modulus and microstructure evolution with sintering, but most of these studies have been carried out beyond 1000°C.…”
Section: Introductionmentioning
confidence: 99%